Examining Transitivity In Arabic And Indonesian Education News And Its Implications For Mahārah al-Qirā’ah - Nurul Fitriyah; Rinaldi Supriadi (Universitas Negeri Semarang, 2026)
Education news in international media plays a role in shaping public understanding of cross-language education policies and issues. Differences in linguistic structure have the potential to affect how reality is represented as well as the level of complexity of readers' understanding. This study aims to compare the transitivity system in Arabic and Indonesian educational news texts on BBC News and examine its implications for maharah qirā'ah. The study uses a descriptive qualitative approach with transitivity analysis in the framework of Systemic linguistics functional. Data in the form of 20 news (10 Arabic and 10 Indonesian) published in 2025–2026 were analyzed to identify the types of process, participants, and circumstances, then compared comparatively. The results showed that Arabic texts were dominated by material process that demanded accuracy in identifying actions and grammatical relationships, while Indonesian texts used more verbal process that emphasized the attribution of information sources. These differences have an impact on the reader's meaning processing strategy. Pedagogically, these findings confirm that learning maharah qirā'ah needs to integrate the practice of automating the recognition of Arabic verbal structures while strengthening the ability to integrate meaning between clauses so that the global understanding of news texts can be achieved effectively.